Constraints on running vacuum models with the baryon-to-photon ratio - Hao Yu; Ke Yang; Jin Li (European Physical Journal C: Particles and Fields, 2022)
Abstract We study the influence of running vacuum on the baryon-to-photon ratio in running vacuum models (RVMs). The photon and baryon number densities, from photon decoupling to the present day, are obtained in the context of RVMs by assuming that photons and baryons can be coupled to running vacuum, respectively. Both cases lead to a time-evolving baryon-to-photon ratio, whose values at different epochs of the universe are strictly constrained by observations. It is found that if the dominant dynamical term of running vacuum is indeed coupled to photons or baryons, the corresponding coefficient must be far less than the upper limit given by previous research, and so it is difficult to distinguish RVMs from the standard $${\varLambda }$$ Λ CDM model. Such RVMs which are barely distinguishable from the $${\varLambda }$$ Λ CDM model seem to be unconvincing. Therefore, if RVMs are reliable cosmological models, running vacuum is unlikely to be coupled to photons or baryons, and then the coefficient of the dominant dynamical term of running vacuum no longer needs to be extremely small.